Backward extraction of jacalin-loaded reverse micelles into new stripping phase and toxicity evaluation on embryonic development of zebrafish - Sy Mohamad, Sharifah Fathiyah; Mohd Said, Farhan; Abdul Munaim, Mimi Sakinah; Mohamad, Shahril; Wan Sulaiman, Wan Mohd. Azizi (Malaysian Society for Biochemistry and Molecular Biology, 2019)
This study demonstrates the effects of aqueous phase pH, KCl concentration and IPA amount on backward extraction efficiency of jacalin from AOT reverse micellar phase into a fresh stripping phase solution. The best condition for backward extraction of jacalin was achieved at the stripping phase pH of 9, 0.75 M KCl and with the addition of 30% v/v IPA. This work also investigates the possible toxicity caused by the backward-extracted jacalin in vivo using zebrafish embryo as a model organism. Our results showed that within the tested concentrations, the purified jacalin had a potentially harmful effect on the embryonic development of zebrafish embryos, as demonstrated by the surviving rates and morphological examination. The survival rate of embryos was found to decrease in concentration and time-dependent manner. The computed LC50 were 20.35, 18.86 and 14.81 µg/ml after exposures of 48, 72 and 96 hours, respectively. Major morphological malformations observed in jacalin-treated embryos were pericardial edema and body curvature for the concentration of jacalin above 12.5 µg/ml. Hence, it can be concluded that the reverse micellar extraction is a suitable method for purification of jacalin from jackfruit seeds, the use of jacalin for therapeutic applications, however, should be done with caution